Reconstructing Ownership and Legal Certainty of Land Experiencing Liquefaction to Protect Community Rights - Antoni, Antoni; Vic, Binsar Jon (Devotion : Journal of Research and Community Service, 2025)
This study aims to examine the impact of liquefaction on land ownership status and reconstruction strategies that can be applied to ensure legal certainty and protection of the rights of affected communities. The liquefaction phenomenon that causes physical changes to the land can eliminate land boundaries and ownership documents, creating legal challenges in determining the status of land ownership after a disaster. The research discusses the laws and regulations governing destroyed land and the land rights elimination based on Government Regulation Number 18 of 2021, as well as the role of the National Land Agency (BPN) in land reconstruction through systematic registration and land redistribution. This study also identifies the importance of mapping technology and participatory approaches in land reconstruction to overcome administrative difficulties and ownership conflicts and provides policy recommendations to ensure the protection of community rights after a liquefaction disaster.